Evaluating the Relationship of Dental Fear with Dental Health Status and Awareness - Yildirim, Tuba Talo (Premchand Shantidevi Research Foundation, 2016)
Introduction: Dental fear is one of the most common problems in dentistry, for both the patient and for the dentist. This issue can have an important effect on an individual's dental health. Aim: The aim of this paper was to report on the prevalence of dental anxiety and to explore if high levels of anxiety are associated with sociodemographic factors, oral health status, and level of oral health awareness. Materials and Methods: The sample for this cross-sectional study included 294 patients (154 males and 140 females). All participants filled out a Dental Fear Survey (DFS) to evaluate their level of dental fear. Gender, age, education level, socioeconomic status and oral health awareness were also noted. Oral health behaviors and oral health awareness levels were investigated using seven questions. Also, the periodontal status of all participants was evaluated using the Community Periodontal Index of Treatment Needs (CPITN). Differences between different subgroups were tested using the chi-square test. Results: There was a statistically significant difference between the DFS groups with regard to sociodemographic data. Women had significantly higher scores than men, and young patients had significantly higher scores than others. Patients with low education levels and low socioeconomic status had high DFS scores. Periodontal status was better in groups that had scores in the low and moderate ranges compared to groups that had high scores on the DFS. There was a statistically significant difference between the groups of DFS and CPITN (p<0.05). Patients with low and moderate levels of DFS answered the oral health knowledge questions correctly. There was a statistically significant difference between the DFS groups based on correct answers to the oral health knowledge questions (p<0.05). Conclusion: The elimination of dental fear is very important and should be treated according to a patient-centered assessment. These individuals were informed about the dental treatment procedure so their prejudices were eliminated. Patients with a high level of dental fear may be given psychiatric support for comfortable treatment procedure.
Keywords: Dental fear survey; Periodontal disease; Periodontal status; Oral health behaviors